Transforming Natural Resources into Business Opportunities through Ecoprint Technique in Sindangmandi Village Banten - Ucu, Ucu; Azzahra, Asri Nur; Fadhilah, Fadhilah; Saputra, Galih Ginanjar (MOVE: Journal of Community Service and Engagement, 2025)
The transformation of natural resources into products of economic value is a strategic step in improving the welfare of village communities. One of the techniques that can be used is ecoprint, which is a method of dyeing fabrics that use natural materials such as leaves and flowers. This community service activity aims to introduce and train ecoprint techniques to housewives and MSME actors in Sindangmandi Village, Banten, as an alternative to environmentally friendly creative businesses. The implementation method includes socialization, demonstration of pounding techniques in ecoprint, and direct practice by participants. The results of the activity show the high enthusiasm of the community in adopting this technique, which is expected to open up new business opportunities based on local resources. With the increase in community skills in ecoprint, the economic potential of the village can develop through the diversification of products such as totebags, hijab, and clothes based on natural dyes. This service contributes to the empowerment of environment-based economies and the sustainability of small businesses at the local level.